The Importance of Vocabulary Development In Reading Comprehension in Efl Classes. - LARABA, Samir (Journal of Human Sciences, 2007)
iIt seems almost impossible to overstate the power of words.  Perhaps the greatest tools we can give students, not only in their education but more generally in life, is a large, rich vocabulary.  This article reports on the importance of vocabulary to reading achievement. Providing vocabulary instruction is one of the most significant ways in which teachers can improve students’ reading comprehension.  Readers cannot understand what they are reading without knowing what most of the words mean. A large vocabulary is more specifically reflective of high levels of reading achievement